RETRACTED: The impact of environmental information disclosure quality on green innovation of high-polluting enterprises - Du, Lizhao; Wang, Xinpu; Peng, Jie; Jiang, Gaoyang; Deng, Suhao (Frontiers in Psychology, 2022)
With the gradual increase of social awareness of environmental protection, environmental information disclosure has become the key for enterprises to accept social supervision and fulfill their social responsibility. Using high-polluting enterprises with Chinese A-share listings from 2008 to 2021, this study examines the impact of environmental information disclosure quality on green innovation. The results show that the improvement of environmental information disclosure quality of high-polluting enterprises can significantly improve the quantity and quality of green innovation of enterprises and are mediated by alleviating financing constraints and enhancing cash reserves. Moreover, improving the quality of environmental information disclosure of highly polluting enterprises has a more significant contribution to the quantity and quality of green patents of non-state owned enterprises, enterprises located in central and eastern China, and large enterprises. The findings of this paper provide theoretical support for achieving a "win-win" situation of environmental protection and green innovation.